Die Entwicklung von Kleinreliefstrukturen im Waldgrenzökoton der Front Range (Colorado, USA) unter dem Einfluss leewärts wandernder Ablegergruppen (PICEA ENGELMANIIl und ABIES LASIOCARPA) - Broll, Gabriele; Holtmeier, Friedrich-Karl (ERDKUNDE, 1994)
Tree islands that originate from layering are typical of the forest-alpine tundra ecotone on Niwot Ridge and other similar wind-exposed ranges in the Rocky Mountains. Dying off at their windward front and elongating by layering at their leeward end, the tree islands slowly move downwind. They strongly influence site conditions (snow cover pattern, thereby distribution of soil moisture and temperature, root growth, nutrient uptake, decomposition etc.) and also the microtopography. As the tree islands grow taller, wind scouring causes windscarps at the wind ward and lateral sides of the islands. After the windward portions of the islands die, the litter layer and Of horizon erode, but at least apart of the Oh horizon is left. Almost simultaneously alpine vegetation invades. Together with the remaining dead wood, invading grasses and herbs not only prevent further deflation but also enhance deposition of fine eolian calcium-rich material ( alpine loess). In the long-term the former tree island site may be separated by lateral erosion into small 10-20 cm high plateaus. Thus microtopography changes conspicuously. Between the scarps still connected with the tree islands and the isolated plateaus differences in soil physical and chemical properties are particularly apparent in the upper part of the soil profile. The profiles of the scarps at the windward side of the former tree islands can be explained by the interaction of soil erosion and accumulation of alpine loess. The other scarps are mostly formed by erosion. Some scarps are likely to be eroded soil profiles of former tree island sites. Close to the windward sides of the tree islands, windscarps which cannot be directly attributed to the downwind migration of the tree islands, probably developed because of erosion that resulted from the disintegration of the cover that had been provided by the alpine vegetation.